2023
DOI: 10.1073/pnas.2218900120
|View full text |Cite
|
Sign up to set email alerts
|

Ecoevolutionary processes structure milk microbiomes across the mammalian tree of life

Abstract: Milk production is an ancient adaptation that unites all mammals. Milk contains a microbiome that can contribute to offspring health and microbial-immunological development. We generated a comprehensive milk microbiome dataset (16S rRNA gene) for the class Mammalia, representing 47 species from all placental superorders, to determine processes structuring milk microbiomes. We show that across Mammalia, milk exposes offspring to maternal bacterial and archaeal symbionts throughout lactation. Deterministic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Substantial immunological and structural changes occur in the skin during metamorphosis [17, 18], and thus developmental shifts in immunity or skin structure may be the mechanisms that drive the assembly of skin bacterial communities. We found that larval newts had the lowest abundances of skin microbes and lower diversity across all metrics (), which may indicate the importance of neutral processes, such as ecological drift and dispersal limitation, in driving early microbial assembly [62]. Conversely, low diversity may indicate strong host selection, though typically microbial diversity decreases with ontogeny as the role of host selection in filtering the microbial community increases [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial immunological and structural changes occur in the skin during metamorphosis [17, 18], and thus developmental shifts in immunity or skin structure may be the mechanisms that drive the assembly of skin bacterial communities. We found that larval newts had the lowest abundances of skin microbes and lower diversity across all metrics (), which may indicate the importance of neutral processes, such as ecological drift and dispersal limitation, in driving early microbial assembly [62]. Conversely, low diversity may indicate strong host selection, though typically microbial diversity decreases with ontogeny as the role of host selection in filtering the microbial community increases [63].…”
Section: Discussionmentioning
confidence: 99%
“…We found that larval newts had the lowest abundances of skin microbes and lower diversity across all metrics ( Fig. 1 ), which may indicate the importance of neutral processes, such as ecological drift and dispersal limitation, in driving early microbial assembly [ 62 ]. Conversely, low diversity may indicate strong host selection, though typically microbial diversity decreases with ontogeny as the role of host selection in filtering the microbial community increases [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used a two-step PCR library preparation and dual-index paired-end sequencing to sequence the skin microbiome of each salamander skin swab sample, as well as positive and negative controls. Briefly, we amplified the V3–V5 region of the 16S rRNA gene (~380 bp) using the universal primers 515F-Y and 939R [ 4 , 5 ], and sequenced the libraries on two MiSeq (Illumina) runs at the Center for Conservation Genomics, NZCBI ( Supplementary Methods 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Host biology is often important in predicting microbial composition and microbiomes typically differ between species [ 4 , 5 , 11 ]. These differences sometimes mirror host evolutionary history—a pattern termed phylosymbiosis—whereby microbiome dissimilarity is correlated with host phylogenetic distance [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many animal species, the perinatal stage is known to be a key period for microbiome influences on both maternal health and appropriate colonization of the infant gut. In mammals, the milk microbiome also plays a key role during the lactation ( Keady et al 2023 ) to influence the microorganisms that take up residence in the newborn gut.…”
Section: Introductionmentioning
confidence: 99%